Analogs, formulations and derivatives of imatinib: a patent review. (2nd December 2015) - Musumeci, Francesca; Schenone, Silvia; Grossi, Giancarlo; Brullo, Chiara; Sanna, Monica
Abstract : Introduction: The Bcr-Abl inhibitor imatinib was approved in 2001 for chronic myeloid leukemia therapy, and dramatically changed the lives of patients affected by this disease. Since it also inhibits platelet derived growth factor receptor (PDGFR) and c-Kit, imatinib is used for various other tumors caused by abnormalities of one or both these two enzymes. Areas covered: This review presents an overview on imatinib formulations and derivatives, synthetic methodologies and therapeutic uses that have appeared in the patent literature since 2008. Expert opinion: Innovative imatinib formulations, such as nanoparticles containing the drug, will improve its bioavailability. Moreover, oral solutions or high imatinib content tablets or capsules will improve patient compliance. Some solid formulations and innovative syntheses that have appeared in the last few years will reduce the cost of the drug, offering big advantages for poor countries. Some recently patented efficacious imatinib derivatives are in preclinical studies and could enter clinical trials in the next few years. Overall, Bcr-Abl inhibitors constitute a very appealing research field that can be expected to expand further.